The Inability Analysis of Catholic Education Institutions on Funding School Operational Especially Regarding Teacher Salaries in Medan - Dionisius Sihombing; Pastor Daniel Erwin Manullang (Budapest International Research and Critics University, 2019)
The purpose of this study is to describe the inability of Catholic education institutions on funding school operations especially regarding teacher salaries in Medan. The main task of the teacher is to do educational assignments. Even though it is not optimal, the cooperation and commitment of all parties involved, especially the institution and the school parties are needed in terms of designing and realizing various collaborative efforts with the church and parents, so that new students will grow in Catholic schools. This study is conducted by using descriptive qualitative approach. The result shows that there is no good achievement without hard work and sacrifice and also a good work approach strategy. Therefore there must be good meetings that create a positive attitude and a sense of belonging to the school, where if the school is successfully developed, all parties will feel the benefits.